Reaksi Spiritualitas: Stimulasi Kehidupan Kerohanian sebagai Upaya Preventif terjadinya Disorientasi di Era Disrupsi Menurut 1 Petrus 2:1-5 - Josua, Rezky Alfero; Kiamani, Andris (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Today’s era of disruption can lead to a decline in spiritual reactions. Intrepeters see the letter of 1 Peter as an example of an appeal to maintain spiritual life in the midst of suffering. Using Exegesis, this article finds the stimulation of spiritual life as a preventive effort for disorientation according to 1 Peter 2:1-5. First, making the word of God as the main need with the metaphor that believers must be like newborn babies who always need pure and spiritual milk to grow. Secondly, approaching Jesus as the living Stone, even though He was rejected by men but His work on the cross shows a living example for every believer and gives eternal life to those who want to believe in Him. Third, following Jesus’ example by being a blessing, for that every believer must join hands in facing the era of disruption with the aim of building a spiritual community as a preventive effort for disorientation. Christians are special group who enjoy spiritual and eternal blessings bestowed by God in Christ, therefore believers must continue to grow more and more like Jesus Christ.